Is All Fair in Law and War? The Legality of Collateral Damage in Targeted Killings with Drones: Discussion Particularly in the Context of the CIA Drone Attacks in Pakistan - Savilaakso, Mira (fi=Turun yliopisto|en=University of Turku|, 2016)
This thesis is interested in the legality of the harm caused to civilians in the context of targeted killings with drone attacks. This issue is researched through the example case of the CIA drone attacks in Pakistan. The chosen legal framework is international humanitarian law, and the legal rules that are applied are the principle of discrimination, the principle of proportionality and the obligation to take precautionary measures in attacks. The first two rules are applied cumulatively so that first the discrimination of targeted killings with drones are researched, after which the proportionality of the attacks is discussed. The aim of this thesis is to find out how the application of proportionality principle differs in the context of targeting fighters of terrorist organizations with drones compared to traditional means and methods of combat used in war fighting. Additionally, the aim is to find out whether the traditional rules of international humanitarian law afford sufficient protection for civilians against disproportionate damage in the special context of targeted killings with drone attacks. The thesis concludes that drones are discriminate and thus lawful means of combat. The method of targeted killings with drone attacks and its special tactics are not generally indiscriminate but the determination should be done on a case-by-case basis. In relation to the proportionality rule, attacks should be proportional in the tactical and in the strategic level of war. However, some of the drone attacks seem to have only insignificant strategic military advantage. Therefore, these attack types – signature attacks – raise concern of disproportion when the insignificant strategic military advantage is compared with collateral damage assessed cumulatively. However, currently the standard of disproportionate drone attack may be that high and ambiguous that the proportionality of an attack is mainly based on the good faith of the attacker that is established by taking precautionary measures. The CIA has made some effort in Pakistan to take precautionary measures. Therefore, the drone attacks may not be considered disproportionate if good faith of the CIA was established. Consequently, I argue that if the precautionary measures were not given that much importance in proportionality analysis, the rule would afford more comprehensive protection for civilians in the context of targeted killings with drone attacks